Avaliação da eficácia de dentifrício de baixa concentração de fluoreto suplementado com hexametafosfato de sódio sobre a desmineralização do esmalte: estudo in vitro - Miyasaki, Marcela Lumi [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The involuntary ingestion of dentifrice by children under six years of age has been considered a risk factor for the development of dental fluorosis. The use of dentifrices with low concentrations of fluoride (F) helps to decrease the ion intake by children who do not yet have full control of expectoration. Recent studies have shown that dentifrice containing 500 μgF/g supplemented with sodium hexametaphosphate (HMP) present similar efficacy of a dentifrice with 1100 μgF/g in the reduction of enamel demineralization in vitro. The objective of this study was to evaluate the efficacy of dentifrices with lower concentrations of F supplemented with different concentrations of HMP on the bovine tooth enamel demineralization through pH cycling model. Enamel blocks were prepared from bovine teeth, surface microhardness was measured and then the blocks were subjected to repeated cycling of alternated pH with daily treatments with dentifrices containing 250 μgF/g between 0 and 3% HMP; A dentifrice without the addition of F and HMP (placebo) and a commercial (Crest , the 1100 μgF/g) were also used. After the pH cycling it was determined the surface microhardness, calculating the percentage change of surface microhardness (% SMH). The results were submitted to ANOVA and Tukey tests and the level of significance was set at 5% (p <0.05). It was observed that the group 250 μgF/g with 0.5% HMP showed lower percentage of surface microhardness change (% SMH), followed by the group of 250 μgF/g with 1.0% HMP that was similar to that Crest . The addition of 0.5% HMP to a dentifrice without F promoted a lower percentage of surface microhardness change compared to placebo. We conclude that it is possible to reduce the concentration of F to 250μgF/g to obtain comparable action of a commercial dentifrice on the demineralization of bovine enamel through the supplementation with hexametaphosphate at concentrations of 0.5 and 1%

A ingestão involuntária de dentifrício por crianças menores de seis anos de idade tem sido considerada como um fator de risco para o desenvolvimento da fluorose dentária. O uso de dentifrícios com concentrações reduzidas de fluoreto (F) contribui para diminuir a ingestão do íon por crianças que ainda não têm controle total da expectoração. Estudos recentes mostraram que dentifrícios contendo 500 μgF/g suplementados com hexametafosfato de sódio (HMP) apresentaram eficácia equivalente a de um dentifrício de 1100 μg F/g na redução da desmineralização do esmalte, in vitro. O objetivo do presente trabalho foi avaliar a eficácia de dentifrícios com 250 μgF/g suplementados com diferentes concentrações de HMP sobre a desmineralização do esmalte de dente bovino, através do modelo de ciclagem de pH. Blocos de esmalte foram obtidos a partir de dentes bovinos, a microdureza da superfície foi medida e, em seguida, os blocos foram submetidos à ciclagens de pH alternadas com tratamentos diários com dentifrícios contendo 250 g F/g e entre 0 e 3% de HMP; foram utilizados também um dentifrício sem adição de F e HMP (placebo) e um comercial (Crest, de 1100 g F/g). Após as ciclagens determinou-se a microdureza de superfície, calculando-se a porcentação de alteração de microdureza de superfície (%SMH). Os resultados foram submetidos aos testes de ANOVA e Tukey, estabelecidos 5% o nível de significância (p<0,05). Observou- se que o grupo 250 gF/g com 0,5% de HMP apresentou menor porcentação de alteração de microdureza de superfície (%SMH), seguido do grupo de 250 gF/g com 1,0% de HMP que ficou semelhante ao Crest (p<0,05). A adição de 0,5% de HMP a um dentifrício sem F promoveu uma menor porcentação de alteração de microdureza de superfície em comparação ao placebo. Conclui-se...
Keywords: Desmineralização do dente; Esmalte dentário; Dentifrícios; Fluoreto de sódio; Fosfatos; Tooth demineralization